EVALUATION OF WASTE BANK PROGRAM IMPLEMENTATION IN PEDURUNGAN KIDUL VILLAGE, PEDURUNGAN SUB-DISTRICT, SEMARANG CITY - Narwastu Widyan Suryaning Asri; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2021)
Waste is one of the crucial issues facing the city of Semarang. In overcoming this, the Semarang City Government is promoting the establishment of waste banks in every kelurahan, one of which is in Pedurungan Kidul Village. In practice, every waste bank must be influenced by several factors that support or hinder the performance of the waste bank. This study aims to analyze the supporting factors and inhibiting factors that affect the implementation of the Waste Bank Program in Pedurungan Kidul Village with reference to four aspects according to the Ministry of Public Works of the Republic of Indonesia. This research uses qualitative methods with descriptivecomparative research design. Data were obtained from observations and interviews with administrators and customers of two Waste Banks in Pedurungan Kidul Village, Pedurungan District, Semarang City. The results showed that there was one supporting factor, namely institutional and three inhibiting factors, namely human resources, facilities and infrastructure, and communication. More inhibiting factors then result in the non-optimal performance of the waste bank. The recommendation that can be given is to diversify social media as a communication strategy between the Environment Agency, the Waste Bank, and the community.